Exposure to Dibutyl Phthalate and Reproductive-Related Outcomes in Animal Models: Evidence From Rodents Study - Wang, Jiawei; Zhang, Xi; Li, Yang; Liu, Yingqing; Tao, Lingsong (Frontiers in Physiology, 2021)
Abstract Background: The role of Dinbutyl phthalate（DBP）exposure in the reproductive system remains controversial. Objective: We therefore performed this meta-analysis to elucidate the associations between DBP exposure and reproductive-related outcome indicators. Methods: We searched relevant literature in PubMed, EMBASE, and Web of science databases. The standardized mean differences (SMDs) and its 95% confidence intervals (CIs) were measured by random-effects models. Publication bias was assessed using funnel plots and Egger's regression test. Results: Based on 19 studies, the results revealed that DBP was significantly associated with negative relation to reproduction organs weight (Testis weight:SMD: -0.59; 95% Cl: -1.23, -0.23; Seminal vesicles weight: SMD: -0.74; 95% Cl: -1.21, -0.27; Prostate weight:SMD: -0.46; 95% Cl: -0.76, -0.16) and sperm parameters (Sperm abnormality: SMD: 1.29; 95% Cl: 0.63, 1.94; Sperm count: SMD: -1.81; 95% Cl: -2.39, -1.23; Sperm motility: SMD: -1.92; 95% Cl: -2.62, -1.23.) Conclusion: Findings from our systematic review suggest that DBP may have negative relation in reproductive system including the decline of testis weight, seminal vesicles weight and prostate weight and impairment of spermatogenesis such as sperm count, sperm motility and sperm abnormalities in animal models.